APLIKASI KONSENTRASI PUPUK PELENGKAP CAIR PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) YANG MENGALAMI CEKAMAN GENANGAN AIR - Nurinsani ' Halily; Gunawan ' Tabrani; Islan ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to get palm oil seedlings goodness although the seedlings in difference level of waterlogging. The experiment has been conducted in the greenhouse Faculty of Agriculture, Riau University, Pekanbaru from December 2015 to March 2016. This study used a completely randomized factorial design consisting of two factors and three replications. The first factor was the concentration of liquid fertilizer(LF) consists of 3 levels p0: No LF, p1: LF 9,000 ppm, and p2: LF 18,000 ppm and the second factor wasthe difference level of waterlogging, consists of 3 levels t0: No waterlogging, t1: Waterlogging to 3cm below of growing point level, t2: Waterlogging 3 cm above of growing point level. The parameters measured were:seedling height, stem diameter, number of leaves, seedling dry weight, shoot root ratio. The mean separation of the tested by Duncan’s new multiple range test  at 5% level. The result showed that no effect of interaction between the difference level of waterlogging and concentration of LF on seedling growth component Tenera palm oil seedling. The waterlogging 3 cm above of growing point level tends to inhibit the growth of seedling i.e. height, dry weight of roots and shoot root ratio of palm oil seedlings. Liquid fertilizer complementary positive effect on the dry weight of oil palm seedlings were experiencing on waterlogging to 3cm below of growing point level, but a negative effect on palm oil seedlings in waterlogging 3 cm above of growing point level.  Keywords: palm oil, waterlogging level, liquid fertilizer